The Effect of Transformational Change on Performance: An Employee’s Stress Appraisals Perspective - Yan, Lei; Wang, Li; Shen, Xiangdong; Li, Pengfei; Guo, Jia (Frontiers in Psychology, 2022)
This study aims to determine the specific impact of employees' perceptions of transformational change on in-role performance and how stress assessment can mediate the relationship between transformational change and in-role performance. According to the cognitive appraisal theory, the same individual has different appraisals of the same stressors, including challenge and hindrance appraisal. As an important stressor, transformational change also affects individuals differently depending on their assessments. This study integrates employees' challenge or hindrance appraisal of transformational change into a conceptual model to distinguish between the roles of the two appraisals. It examines it as a mediating mechanism between transformational change and in-role performance. Additionally, 313 employees who recently experienced transformational change were used as samples to test the hypothesis. The results show that transformational change negatively affects employees' in-role performance; hindrance appraisal negatively mediates the relationship between transformational change and in-role performance, and challenge appraisal positively mediates the relationship between transformational change and in-role performance. The originality and value of this research extend the application of stress appraisals in organizational change management. Research shows that, in the context of major change, employees' in-role performance is reduced by the impact of transformational change. However, when employees positively appraise organizational change, the negative effects of change are weakened.